2004
DOI: 10.1021/ja038812t
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diastereoselective Heterogeneously Catalyzed Hydrogenation of Enamines for the Synthesis of Chiral β-Amino Acid Derivatives

Abstract: Pure (Z)-enamines readily prepared from beta-ketoesters and amides using (S)-phenylglycine amide were hydrogenated with very high diastereoselectivities (up to 200:1) using heterogeneous catalysis. Hydrogenolytic cleavage of the (S)-phenylglycine amide afforded the corresponding chiral beta-aminoesters and amides. The high geometrical purity of the (Z)-enamine and a simple activation procedure for the PtO2 catalyst are essential in achieving high selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 19 publications
0
33
0
3
Order By: Relevance
“…However, the preparation of b-amino acids continues to rely principally on the resolution of racemates [105] or on the use of chiral auxilaries. [106] The application of catalytic asymmetric hydrogenation has been hindered by the assumption that protection of the nitrogen atom is required to achieve high levels of selectivity by virtue of the formation of a six-membered ring chelate between the substrate and the metal. Hsiao et al at Merck showed that in the presence of Josiphos ligands 120 and 121, highly selective catalysts generated from [{RhCl(cod)} 2 ] reduced unprotected b-enamine esters 122 and amides 124 to the corresponding bamino acid derivatives 123 and 125, respectively (Scheme 56).…”
Section: A K Yudin and N A Afaghmentioning
confidence: 99%
“…However, the preparation of b-amino acids continues to rely principally on the resolution of racemates [105] or on the use of chiral auxilaries. [106] The application of catalytic asymmetric hydrogenation has been hindered by the assumption that protection of the nitrogen atom is required to achieve high levels of selectivity by virtue of the formation of a six-membered ring chelate between the substrate and the metal. Hsiao et al at Merck showed that in the presence of Josiphos ligands 120 and 121, highly selective catalysts generated from [{RhCl(cod)} 2 ] reduced unprotected b-enamine esters 122 and amides 124 to the corresponding bamino acid derivatives 123 and 125, respectively (Scheme 56).…”
Section: A K Yudin and N A Afaghmentioning
confidence: 99%
“…Treatment of the corresponding β‐ketoester or ‐amide with the chiral auxiliary ( S )‐phenylglycinamide provides the substituted Z ‐enamide 99 . Hydrogen bonding results in a rigid conformation of 99 , with the phenyl substituent on the auxiliary shielding the top face of the molecule, which results in stereoselectivities of up to 200:1 being obtained in the hydrogenation over PtO 2 (Scheme ) 174a. Pretreatment of the catalyst with acetic acid was found to be very important for good catalytic activity.…”
Section: Diastereoselective Heterogeneous Catalysismentioning
confidence: 99%
“…[15] The reduction of (S)-phenylglycine dehydro-β-amino esters or dehydro-β-aminoamides with PtO 2 has been reported on and proceeds in very good ee, but in low overall yield from the starting β-keto esters. [16] Herein, we report on the reductive amination of keto esters 1 with (R)-or (S)-α-MBA to generate amino esters 2 using heterogeneous hydrogenation catalysts (optimally Raney-Ni) with a Brønsted acid (optimally AcOH) for α-and β-keto esters, and with a Lewis acid [optimally Ti(OiPr) 4 ] for a γ-keto ester.…”
Section: Introductionmentioning
confidence: 99%